2014
DOI: 10.1186/1748-717x-9-155
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery (SRS) for brain metastases: a systematic review

Abstract: In many patients with brain metastases, the primary therapeutic aim is symptom palliation and maintenance of neurologic function, but in a subgroup, long-term survival is possible. Local control in the brain, and absent or controlled extracranial sites of disease are prerequisites for favorable survival. Stereotactic radiosurgery (SRS) is a focal, highly precise treatment option with a long track record. Its clinical development and implementation by several pioneering institutions eventually rendered possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 107 publications
1
104
0
1
Order By: Relevance
“…8 For framed SRS, 1-year local progression-free survival (PFS) was reported to be up to 70% to 90%, and median overall survival (OS) of 6 to 12 months. [9][10][11][12][13][14][15] The outcomes of frameless SRS have been reported only in limited series, with 1-year local control of 79% to 95%. 5,[16][17][18] Patient selection and tailor-made management are indeed challenging.…”
Section: New Knowledge Added By This Studymentioning
confidence: 99%
“…8 For framed SRS, 1-year local progression-free survival (PFS) was reported to be up to 70% to 90%, and median overall survival (OS) of 6 to 12 months. [9][10][11][12][13][14][15] The outcomes of frameless SRS have been reported only in limited series, with 1-year local control of 79% to 95%. 5,[16][17][18] Patient selection and tailor-made management are indeed challenging.…”
Section: New Knowledge Added By This Studymentioning
confidence: 99%
“…Brain metastases are a common oncological diagnosis1 and intracranial stereotactic radiosurgery (SRS) has evolved as an important modality of treatment/palliation for that disease 2, 3. It was demonstrated that even with multiple metastases the SRS treatment could provide reasonable local control,4, 5 and a multi‐institutional observational study suggested that clinical outcomes for patients with 5–10 individual metastases treated by SRS alone may be non‐inferior to those with 2–4 targets 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Patients can be treated in a minimally invasive fashion and return to usual activities the next day. GKRS has found applications as a primary strategy or adjuvant therapy in a number of clinical fields including intracranial tumors, vascular malformations, psychiatric disorders, and functional disorders such as pain, movement disorder, and epilepsy (21)(22)(23)(24)(25). Despite risks of radiation-induced adverse effects, GKRS is now an indispensable neurosurgical tool, especially in cases where the lesion is too hard to approach with standard neurosurgery and the patient's condition not good enough to endure open surgery (26).…”
Section: Gamma Knife Radiosurgery (Gkrs)mentioning
confidence: 99%